International Proceedings on Advances in Soft Computing, Intelligent Systems and Applications ASISA 2016 (Advances in Intelligent Systems and Computing,, 2018)
The book focuses on the state-of-the-art technologies pertaining to advances in soft computing, intelligent system and applications. The Proceedings of ASISA 2016 presents novel and original work in soft computing, intelligent system and applications by the experts and budding researchers. These are the cutting edge technologies that have immense application in various fields. The papers discuss many real world complex problems that cannot be easily handled with traditional mathematical methods. The exact solution of the problems at hand can be achieved with soft computing techniques. Soft computing represents a collection of computational techniques inheriting inspiration from evolutionary algorithms, nature inspired algorithms, bio-inspired algorithms, neural networks and fuzzy logic.